Mercury in the diet, absorption and bio accessibility - Abdullah, Najwa (Technium BioChemMed, 2020)
The human body is exposed to significant amounts of the potent inorganic mercury (Hg+2) or methylmercury (Me-Hg). The diet is the main route for this exposure; the fish consumption may result with confusion for the crucial benefits of the fish consumption beside the hazardous side of their content of mercuric compounds. The mercuric compounds have different routes of absorption, mostly by the gut through the diet, causing severe health problems via the oxidative stress mechanisms. The diet complexity regarding ingredients and cooking type may affect the bioaccessibility of the present mercuric compounds by several mechanisms, in addition to the protective role of gut microbiota. The aim of this review is to explore the available data and researches, about the mercuric present forms, absorption pathways, toxicity mechanisms and dietary components that negatively affect the mercuric compounds bioaccessibility (absorption) including the cooking type, fat content, omega-3 fatty acids, selenium, glutathione, gut microflora, ethanol content, garlic, onion, tea, coffee, and fruits.